Intensive and critical care nurses’ compliance, barriers, and challenges with ventilator-associated pneumonia prevention: a cross-sectional study - Hazel Novela Villagracia; Tahani Nasser Alhejaili; Bushra Alshammari; Salwa Abd El Gawad Sallam; Awatif Mansour Alrasheeday; Lea L. Dando; Odeta A. Nacubuan; Habib Alrashedi; Shaimaa Mohamed Nageeb; Larry Terence O. Cornejo; Rico William A. Villagracia; Soha Kamel Mosbah Mahmoud; et al. (BMC Nursing)
Abstract Background Ventilator-associated pneumonia (VAP) poses a significant challenge in critical care settings, impacting patient outcomes and healthcare costs. In Saudi Arabia, several studies have reported concerns regarding VAP, including variable VAP rates, inconsistent compliance with and knowledge of VAP prevention practices, and inadequate national data. Objectives To investigate the intensive and critical care nurses’ (ICCNs) self-reported perceived compliance with VAP prevention guidelines, barriers and challenges in caring for mechanically ventilated patients, the demographic variables that associate compliance and factors affecting VAP prevention, and the association between perceived compliance and the barriers affecting the care of mechanically ventilated patients. Methods A descriptive, correlational, and cross-sectional design was used. ICCNs (n = 152) were conveniently recruited from two tertiary government-owned hospitals. Data were collected using self-report scales from April to June 2024. Descriptive and inferential statistics were used for data analyses. Results Findings showed that 43% of ICCNs had high compliance with VAP prevention guidelines. The use of protective gloves at every approach to a patient (96.70%) was the VAP guideline that received the highest perceived compliance among ICCNs. Meanwhile, those with 11 to 15 years of experience were more compliant (p = 0.023) than other groups and demographics. Major barriers to compliance included nursing staffing shortages (94.10%) and limited resources (75.00%). Only ICCNs with 11 to 15 years of experience showed greater awareness of VAP prevention guidelines (p = 0.023). Nurses’ nationality, i.e., non-Saudi nurses (p = 0.024) and higher educational levels (p = 0.005), demonstrated greater awareness of barriers to managing and caring for mechanically ventilated patients. ICCNs perceived barriers negatively influenced their perceived compliance with VAP prevention (p = 0.002), indicating that increased barriers are associated with lower compliance. Finally, the considerable challenges in VAP prevention were time constraints and the need for more communication among the health team. Conclusion Staffing shortages and resource limitations impacted ICCNs’ compliance with VAP prevention guidelines. Furthermore, they became less compliant with higher VAP barrier perceptions. Time constraints and team communication were considerable challenges in VAP prevention. As a result, nurse managers could create comprehensive programs like long-term VAP prevention training and interdisciplinary collaboration in the ICU. Healthcare organization administrators should enhance resource allocation and policy formulation to foster compliance. Clinical trial number Not applicable.